KEHIDUPAN SOSIAL EKONOMI KELUARGA PETANI DALAM MENINGKATKAN TARAF HIDUP (Studi di Desa Bapa Distrik Bogonuk Kabupaten Tolikara Propinsi Papua) - Wanimbo, Enues (HOLISTIK, Journal Of Social and Culture, 2019)
Rural communities in general are people who use natural resources in the field of agriculture. Land is a renewable natural resource, but because the amount that still causes land has a strategic role in human life, with the increasing number of people causing more and more gaps in the land. The existence of land resource inequality will cause mastery over the land in the community, this is what can lead to changes in social and economic status in the community. One aspect of the field of agriculture is to see the socio-economic aspect, because the socio-economic aspect is an important factor in agriculture.The presence of traditional tribes in the village of Bapa Tolikara Regency is very helpful farming activities. Actually, farmers are intensified in institutional, it will spur social change for farmers ' own people. In socio-economic life for farmers ' families, from the farming aspect, the mental aspect, the aspect of education and the direct aspects of income, also affects the living standards of the farmer's family.In fulfilling the socio-economic life of the farmer family still have constraints on agricultural field efforts. 1) Issue of farmer Business Capital 2). Marketing issue of production results 3) farmer institutional Issue 4) The problem has not been effective agricultural counseling as an aspect of farmer empowerment.Agricultural field has an important meaning for the life of farmers in improving its business. That means the better the family life of farmers will affect the improvement of family welfare.Â Keywords: family, agriculture, farmers